The Effect of Circuit Games on Physical Fitness in Upper Class Students at SDN Tanggungan Gudo Jombang - Nurdian Ahmad; Dwi Septiyawan; Mecca Puspitaningsari (Universitas Majalengka, 2023)
Circuit game is a form of game that is carried out in one round through several posts, at each post students perform various forms of games that are varied and carried out repeatedly. The purpose of this study was to determine the effect of circuit games on physical fitness of students at SDN Gudo Jombang. This type of research used is quantitative research. The experimental research design used was pretest and posttest data. The population in this study consisted of 80 upper class students at Tangngungan Gudo Jombang Elementary School. The data analysis technique used in the research uses the T test. In data analysis, the steps that must be started are data description, then normality test, homogeneity test and hypothesis testing are carried out. Based on the results of the hypothesis test that tcount = 26.107 > 2.045, it can be concluded that ha is accepted, meaning that there is an effect of circuit games on physical fitness. Based on the results of this study, it can be concluded that there is an effect of circuit games on physical fitness of students at SDN Gudo Jombang